Aonla rust, its causes, epidemiology and management- A review (Indian Journal of Arid Horticulture, 2025)
Aonla or Indian Gooseberry is an important fruit crop grown in the Indian sub continent, celebrated for its exceptional nutritional and rejuvenating properties and  highly valued in Unani and traditional Indian medicine for its medicinal benefits.  However, Aonla rust caused by the fungus Ravenelia (Phakopsora) emblicae, poses  significant threat to productivity of this fruit crop as it can severely impact crop yield  and quality, leading to economic losses for farmers. This fungal disease thrives in  warm, humid conditions and is exacerbated by factors such as improper planting  density and poor water management. The effects of Aonla rust include reduced fruit  production, lower fruit quality, and overall tree health decline, ultimately affecting the  economic viability of Aonla farming. Effective management of Aonla rust involves  a combination of cultural practices, chemical treatments, use of bioagents and the  use of resistant varieties. The common chemical treatment interventions involve  foliar application of wettable sulphur / Mancozeb 75 WP/ Chlorothalinil @ 0.2% and  Copper oxychloride 50 WP @ 0.3% at 10-12 days’ intervals starting in August. Bio agents such as Trichoderma harzianum and Pseudomonas fluorescens and organic  pesticides like neem oil, NSKE, and neem leaf extract have also been proven effective  in disease control. Strategies such as proper spacing, pruning, and the application of  fungicides are essential in disease management. Additionally, the development and  use of rust-resistant Aonla varieties is crucial for sustainable production. Ongoing  research and integrated disease management approaches will be key to mitigating  the impact of Aonla rust and ensuring the continued success of Aonla cultivation.
Keywords: Aonla Rust; Ravenelia emblicae; Fungal Disease; Crop Management